ETIKA KONSERVASI BANGUNAN - Aswar Husen Buton; Putu Ayu P. Agustiananda; Arif Budi Sholihah (RUSTIC, 2022)
The Dutch heritage that can be found in Buru Regency is the former residence of the Dutch controller. This building has historical value for Buru Regency because it is estimated that it has been established since the early 20th century and is still used today as the Office of the Civil Service Police Unit. Reuse or adaptive re-use is intended to maintain the sustainability of the building, but in doing so there are conservation ethics that must be considered so that the preservation can run well. Therefore, this study was conducted with the aim of finding out whether or not the ethics of conservation in the former Dutch controller's residence were appropriate by conducting literature studies, observing local libraries and building locations directly, and conducting interviews with building users. The results of this study found that most of the conservation ethics in the former Dutch controller's residence were not met, although some had been fulfilled.